Pengaruh Pola Asuh Perempuan Muslim Pekerja terhadap Pendidikan Anak - Hartati, Sri; Azis, Abdul; Endang, Ujang (Bestari, 2020)
The purpose of this study was to determine the parenting style of working women outside the home and children's education in Kedungcaung Hamlet, Karangkamulyan Village, Cijeungjing District, Ciamis Regency, and to determine the effect of caring for women workers outside the home on children's education in Kedungcaung Hamlet, Karangkamulyan Village, Cijeungjing Village, Ciamis Regency. This research uses quantitative research with correlational methods. The data collection techniques and instruments used were questionnaires. The data analysis used is descriptive statistics and inferential statistics. Inferential statistics using normality test, linearity test and hypothesis testing. The hypothesis test used is the Pearson Product Moment correlation. After analyzing the data, the results show that: 1) The pattern of caring for female workers outside the home in Kedungcaung Hamlet, Karangkamulyan Village, Cijeungjing District, Ciamis Regency is classified as moderate, because the mean value is 47.69. This figure is in the range of scores of 45.26 - 50.12. 2) The education of children in Kedungcaung Hamlet, Karangkamulyan Village, Cijeungjing District, Ciamis Regency is classified as moderate, because the mean is 49.81. This figure is in the range of scores of 47.34 - 52.28. 3) The pattern of caring for female workers outside the home affects children's education because the probability value of 0.05 is greater than the probability value of Sig or [0.05> 0.000]. The correlation is strong because it gets a score of 0.789. The contribution (contribution) to the care of women working outside the home to children's education, namely 62.3% and the remaining 37.7% is determined by other variables not discussed in this study.